Potential Precursor of Angiotensin-I Converting Enzyme (ACE) Inhibitory Activity and Structural Properties of Peptide from Peptic Hydrolysate of Cutlassfish Muscle. Issue 6 (2nd July 2020) - Kim, Hyun-Soo; Lee, WonWoo; Jayawardena, Thilina U.; Kang, Nalae; Kang, Min Cheol; Ko, Seok-Chun; Lee, Jeong Min; Yim, Mi-Jin; Lee, Dae-Sung; Jeon, You-Jin
ABSTRACT: Peptic hydrolysates were prepared by digesting the cutlassfish muscle protein using pepsin for 1, 3, and 6 h, and their inhibitory activity against angiotensin-I converting enzyme (ACE) was studied. The ACE-inhibitory effect of the peptic hydrolysate of cutlassfish muscle generated at the 3 h time point exhibited the strongest activity. After identifying the optimal hydrolysate, the active peptide was isolated by ultrafiltration, gel permeation, and high performance liquid chromatography (HPLC). The resulting purified peptide was characterized using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF/TOF MS/MS) and was identified to be a 496.44 Da pentapeptide (Phe-Ser-Gly-Gly-Glu). The ACE-inhibitory activity of the active peptide exhibited an IC50 value of 0.033 ± 0.003 mg/ml. A molecular docking program was used to simulate the interaction between the peptide and ACE, which revealed that the inhibitory effect was mainly due to the hydrogen bonds between ACE and the peptide. Based on the ACE-inhibitory properties and the molecular docking study of the resulting active peptide, we demonstrated an increase in nitric oxide (NO) production in a dose-dependent manner. In conclusion, cutlassfish protein hydrolysate and the resulting active peptide could be used as active ingredients in functional food as anti-hypertensive agents.